Infantile Fibrosarcoma With NTRK3-ETV6 Fusion Successfully Treated With the Tropomyosin-Related Kinase Inhibitor LOXO-101 - Nagasubramanian, Ramamoorthy; Wei, Julie; Gordon, Paul; Rastatter, Jeff C.; Cox, Michael C.; Pappo, Alberto (Pediatric blood & cancer, 2016)
Infantile fibrosarcoma (IFS) is a rare pediatric cancer typically presenting in the first 2 years of life. Surgical resection is usually curative and chemotherapy is active against gross residual disease. However, when recurrences occur, therapeutic options are limited. We report a case of refractory IFS with constitutive activation of the tropomyosin‐related kinase (TRK) signaling pathway from an ETS variant gene 6–neurotrophin 3 receptor gene (ETV6–NTRK3) gene fusion. The patient enrolled in a pediatric Phase 1 trial of LOXO‐101, an experimental, highly selective inhibitor of TRK. The patient experienced a rapid, radiographic response, demonstrating the potential for LOXO‐101 to provide benefit for IFS harboring NTRK gene fusions.